The Impact of Exposure to Online Advertising on the Intention to Download Online Loan Applications among Young Adults (18-27 Years) in Indonesia - Pranata, Fahmi Aji; Salehudin, Imam (Politeknik Negeri Bandung, 2024)
This study explores the determinants of Generation Z's (Gen-Z) intention to download online loan applications in Indonesia, with a focus on the impact of online loan advertisements. The research aims to evaluate how elements such as informativeness, entertainment, irritation, and incentives within advertisements influence the perceived value of these ads and, consequently, the download intention. Utilizing Partial Least Squares-Structural Equation Modeling (PLS-SEM), data was analyzed from respondents aged 18-27. The findings reveal that incentives are the most influential factor driving download intention, while perceived advertisement value, risk, and trust serve as pivotal mediators. The study suggests that online loan advertisers should highlight positive attributes of their ads and minimize irritation to improve engagement and build trust among Gen-Z consumers. These insights enhance the understanding of digital marketing strategies and consumer behavior in the financial technology sector.